2017
DOI: 10.1371/journal.pgen.1006654
|View full text |Cite
|
Sign up to set email alerts
|

CUZD1 is a critical mediator of the JAK/STAT5 signaling pathway that controls mammary gland development during pregnancy

Abstract: In the mammary gland, genetic circuits controlled by estrogen, progesterone, and prolactin, act in concert with pathways regulated by members of the epidermal growth factor family to orchestrate growth and morphogenesis during puberty, pregnancy and lactation. However, the precise mechanisms underlying the crosstalk between the hormonal and growth factor pathways remain poorly understood. We have identified the CUB and zona pellucida-like domain-containing protein 1 (CUZD1), expressed in mammary ductal and alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The Jak-STAT signaling pathway is an essential pathway for PRL induction [35]. PRL can stimulate the STAT5 pathway to affect cell proliferation and differentiation [36]. In this study, we used the STAT5 inhibitor to verify the effect of prolactin on the expression of circHIPK3.…”
Section: Discussionmentioning
confidence: 99%
“…The Jak-STAT signaling pathway is an essential pathway for PRL induction [35]. PRL can stimulate the STAT5 pathway to affect cell proliferation and differentiation [36]. In this study, we used the STAT5 inhibitor to verify the effect of prolactin on the expression of circHIPK3.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation results show that CUZD1 forms a complex with JAK2 and STAT5, and CUZD1 FIGURE 1 | Novel components of the JAK2-STAT5 signaling pathway. CPAP, centrosomal P4.1-associated protein; CypA, cyclophilin A; CUZD1, zona pellucida-like domain-containing protein 1; JAK2, Janus kinase 2; NcoA, nuclear receptor co-activator; PIKE-A, PI 3-kinase enhancer A; PlrR, prolactin receptor; STAT5, signal transducers and activators of transcription 5. knockout disrupts the connection between JAK2 and STAT5 (Mapes et al, 2017). In addition, PIKE-A has also been reported to participate in complex formation with PRLR and STAT5, which is required for activation of the PRLR and STAT5 signaling pathways (Chan et al, 2010).…”
Section: Novel Factors In Jak2-stat5 Activationmentioning
confidence: 99%
“…CUZD1 knockout abolishes STAT5 phosphorylation and impairs mammary ductal branching and alveolar development. However, CUZD1 overexpression in mammary epithelial cells increases STAT5 phosphorylation ( Mapes et al, 2017 ). Immunoprecipitation results show that CUZD1 forms a complex with JAK2 and STAT5, and CUZD1 knockout disrupts the connection between JAK2 and STAT5 ( Mapes et al, 2017 ).…”
Section: Novel Factors In Jak2-stat5 Activationmentioning
confidence: 99%
“…The TGF-β family members play an important role in ductal differentiation and branching morphogenesis; besides their involvement in malignant ductal tissue patterning [76]. It is observed that the protein termed CUB and zona pellucida-like domain-containing protein 1 mediates its function to control gland development through JAK2-STAT5 pathway during conception [77]. The IGF1 is essential for lobule and alveoli development [78].…”
Section: Growth Factors and Cytokines Involvedmentioning
confidence: 99%